Improving Learning Results with Make A Match Method - Lusia Ida Mawarsih (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is a literature study that aims to determine the improvement of learning outcomes after applying the make a match learning model, the object of this research is Classroom Action Research and related books, the data collection technique in this study is descriptive qualitative analysis. The results of the analysis in this study indicate that there is an increase in using the make a match learning model, the average percentage of learning outcomes through the make a match model, researchers get an increase from 44% after using the make a match learning model to 89%, so it can be concluded that the make a match learning model can improve student learning outcomes.